2019
DOI: 10.1371/journal.pone.0218629
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the metal-dependent structural and functional properties of mouse and human SMP30

Abstract: Senescence Marker Protein (SMP30) is a metalloenzyme that shows lactonase activity in the ascorbic acid (AA) biosynthesis pathway in non-primate mammals such as a mouse. However, AA biosynthesis does not occur in the primates including humans. Several studies have shown the role of SMP30 in maintaining calcium homeostasis in mammals. In addition, it is also reported to have promiscuous enzyme activity with an organophosphate (OP) substrate. Hence, this study aims to recombinantly express and purify the SMP30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In addition to the above described enzymes, several proteins have been shown to possess a moonlighting OP hydrolyzing activity. For instance, senescence marker protein (SMP30) isolated from mouse liver cytosol, is capable of hydrolyzing DFP and other OPs such as sarin, soman, and tabun (Scott and Bahnson, 2011; Dutta et al, 2019). Although SMP30 can hydrolyze similar substrates like DFPase, it is not a calcium binding protein, and shows activity in the presence of Mg 2+ and Mn 2+ (Dutta et al, 2019).…”
Section: Enzymes For Decontaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above described enzymes, several proteins have been shown to possess a moonlighting OP hydrolyzing activity. For instance, senescence marker protein (SMP30) isolated from mouse liver cytosol, is capable of hydrolyzing DFP and other OPs such as sarin, soman, and tabun (Scott and Bahnson, 2011; Dutta et al, 2019). Although SMP30 can hydrolyze similar substrates like DFPase, it is not a calcium binding protein, and shows activity in the presence of Mg 2+ and Mn 2+ (Dutta et al, 2019).…”
Section: Enzymes For Decontaminationmentioning
confidence: 99%
“…For instance, senescence marker protein (SMP30) isolated from mouse liver cytosol, is capable of hydrolyzing DFP and other OPs such as sarin, soman, and tabun (Scott and Bahnson, 2011; Dutta et al, 2019). Although SMP30 can hydrolyze similar substrates like DFPase, it is not a calcium binding protein, and shows activity in the presence of Mg 2+ and Mn 2+ (Dutta et al, 2019). Bacterial lactonases have also shown potential as OP-degrading enzymes due to their high degree of substrate promiscuity (Draganov, 2010).…”
Section: Enzymes For Decontaminationmentioning
confidence: 99%
“…SMP30 is abundantly expressed in kidney proximal tubule cells, and its expression decreases with age. Loss of SMP30 is associated with kidney damage in several mouse models ( Yumura et al., 2006 ; Kondo et al., 2013 ; Miyata et al., 2013 ; Okada et al., 2015 ; Kondo and Ishigami, 2016 ; Yamauchi et al., 2016 ; Dutta et al., 2019 ). However, we did not find reduced SMP30 expression in mouse kidney and NRK cells.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it is located at p11.3-q11.2 of the X chromosome [ 114 ]. Like PON1, it has also been reported to show lactonase [ 116 ] activity as its physiological function; however, it also catalyses the hydrolysis of an OPC, diisopropyl fluorophosphate, thus acting as DFPase [ 117 ]. SMP30 is also referred to as regucalcin due to its high affinity with calcium indicating its role in maintaining calcium homeostasis in the cells [ 118 120 ].…”
Section: Treatment Strategies For Organophosphorus Poisoningmentioning
confidence: 99%
“…These analyses suggest that SMP30 might play an important role in calcium homeostasis and providing protection against OPC poisoning in human. A recent study from our research group demonstrated that both mouse and human SMP30 showed organophosphate hydrolase activity in the presence of Ca 2+ and Zn 2+ , thus displaying metal-dependent promiscuous activity [ 116 ]. A recombinant HuSMP30 has also been expressed with chaperones as a soluble protein and has been characterized for its DFPase activity [ 122 ].…”
Section: Treatment Strategies For Organophosphorus Poisoningmentioning
confidence: 99%